Effects of Drought Stress on Key Enzymes in Soybean Carbon and Nitrogen Metabolism - Qu, Z.P.; Zhou, X.Y.; Liu, C.X.; Wang, X.Y.; Dong, Shoukun (Legume research, 2024)
Background: The synthesis and catalysis of enzymes are inherently linked to the presence of water and drought-induced water deficit in plants can adversely impact enzyme activity. Drought severely impairs the growth and development of crops, with the extent of its impact varying according to the severity of the water scarcity. Drought also regulates the activity of carbon and nitrogen metabolizing enzymes in plants. Methods: To investigate the effects of varying degrees of drought on soybeans, this study selected HN44 (drought-resistant variety) and HN65 (drought-sensitive variety) as subjects through sand culture and assessed the changes in key enzymes involved in carbon and nitrogen metabolism within the soybean leaves in 2022. Result: The results indicated that short-term drought stress increased the activities of sucrose synthase (SUS), Sucrose Phosphate Synthase (SPS) and Glutamine Synthetase (GS), while decreasing the activity of nitrate reductase (NR). In contrast, prolonged drought reduced the activities of SUS and GS. This study provides a theoretical foundation for enhancing the drought stress resistance of soybeans.